Examining environmental constraints in sport: Spin characteristics of two cricket pitches with contrasting soil properties. Issue 8 (13th September 2020) - Crowther, Rian H.; Gorman, Adam D.; Spratford, Wayne A.; Sayers, Mark G.; Kountouris, Alex
Abstract: In the sport of cricket, the pitch is an organic surface that represents an important environmental constraint. While the soil properties of the pitch are known to influence the pace and bounce of medium and fast deliveries, it is unknown how the soil constructs or the seam of the cricket ball affect the pace, bounce, and deviation of a spinning delivery. A specialised spin bowling machine was used to deliver 276 (139 wrist spin, 137 finger spin) spinning deliveries onto two cricket pitches with contrasting soil properties. The pitches included a bespoke international pitch (BIP; higher sand content at 43.28%) and a common Australian pitch (CAP; lower sand content at 7.44%). Results indicated that the BIP showed significantly slower reflection pace and larger deviation, compared to the CAP. Irrespective of the pitch type, when the seam of the ball impacted the pitch, there was a significantly slower reflection pace and larger deviation. The reflection properties of the BIP resembled that of a "spinning pitch" which can be used as a form of representative practice for conditions similar to those that may be experienced in India. The impact of the seam on the pitch surface significantly altered the reflection of the ball and should be considered in future cricket research.